Produção sustentável do mel nas ilhas do Rio Paraná: gestão, tecnologia de produção e qualidade do mel - Hanel, Samoel Nicolau (2017)
The honey of bees has its composition varying according to the botanical origin, the bee species and the climatic conditions of the region where it was produced. The article presents information on the physical-chemical characteristics survey and the production and management system of beekeepers living in the Paraná River islands, Guaíra / PR. The objective of this study was to perform physicochemical analyzes of honey considering the moisture content, pH, hydroximetifurfural (HMF), acidity, diastasis, sugars and sucrose. The honey samples were collected in apiaries of thirty-one apiaries from the islands of the Paraná River. The production of honey was concentrated in six beekeepers, and its location was georeferenced. The results of the study of the physical-chemical characteristics of 31 honey samples from the Paraná River micro-region showed that: a) only 4 samples were within the legal limit of humidity, 18 g / 100 g, and the sample with the highest content Humidity was 25g/ 100g; B) for sugar, all results were in compliance with the regulations; C) for the sucrose content, only 6 samples exceeded the limit value; D) with regard to the acidity indexes, it was verified that all analyzes carried out were within the legal facets of normative instruction nº 11; E) in relation to HMF, only one sample exceeded that allowed by the regulations; F) in the diastasis activity, it was verified that only one analysis was below the allowed parameters; G) for pH, all analyzes were in accordance with the honey production regulations. It was concluded that in the Brazilian market honey is recognized worldwide, according to Apicultural Products, and also as the largest potential supplier of bee products, because it is notably favored by biodiversity and climate. Brazilian honey exports have grown significantly in recent years, and more needs to be invested in public policies and management for sustainable development.